An allosteric ribozyme generator and an inverse folding ribozyme generator: Two computer programs for automated computational design of oligonucleotide-sensing allosteric hammerhead ribozymes with YES Boolean logic function based on experimentally validated algorithms. (June 2022) - Kaloudas, Dimitrios; Penchovsky, Robert
Abstract: Designing oligonucleotide-sensing ribozymes using computational approaches is advantageous to in vitro selection methods for efficiency and accuracy. Allosteric ribozymes can be computationally designed for various applications in gene therapy, designer gene control systems, biosensors, and molecular computation. Here we present two programs, the allosteric Ribozyme Generator (RG) and the Inverse Folding Ribozyme Generator (IFRG), engineered to generate allosteric ribozymes with YES logic. The RG computes allosteric ribozyme sequences' secondary structure using the minimal sequence of the hammerhead ribozyme by inserting oligonucleotide binding site (OBS) elements in the second stem. The IFRG program uses inverse folding to generate allosteric ribozyme sequences with OBS bearing distinct sequences and similar folding. For the generation of the OBS sequences, random search algorithms are employed. Allosteric ribozyme sequences generated by the RG can be used as a matrix for the IFRG program. This approach applies RNA-folding algorithms based on applying thermodynamic parameters using the partition function of the RNAfold, and the RNAinverse source codes from the Vienna RNA folding package. The two algorithms apply dynamic programming and random search algorithms to generate in silico allosteric ribozymes with predefined properties within minutes using a personal computer with over 90% accuracy, without high computation power as experimentally validated and published by us previously. Graphical abstract: Image 1 Highlights: Computational design of allosteric ribozymes. Synthetic hammerhead ribozymes with YES Boolean logic function. Oligonucleotide-sensing ribozymes. Software for allosteric ribozyme generation under Linux. Software for inverse allosteric ribozyme generation under Linux.